2008
DOI: 10.1128/aac.01052-07
|View full text |Cite
|
Sign up to set email alerts
|

Role of the AheABC Efflux Pump in Aeromonas hydrophila Intrinsic Multidrug Resistance

Abstract: Gene inactivation and complementation experiments showed that the tripartite AheABC efflux pump of Aeromonas hydrophila extruded at least 13 substrates, including nine antibiotics. The use of phenylalaninearginine-␤-naphthylamide (PA␤N) revealed an additional system(s) contributing to intrinsic resistance. This is the first analysis of the role of multidrug efflux systems in Aeromonas spp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 22 publications
1
31
0
2
Order By: Relevance
“…For example, 8.4 µM and 50 µM of TBT were considered the barrier of toxic concentrations by Wuertz et al (1991) (Mendo et al, 2003;Cruz et al, 2007) which can be related with the different architecture of the bacterial cell wall. According to the literature, the highest TBT concentration tested was about 3 mM (Cruz et al, 2007;Hernould et al, 2008). At this concentration two Gram negative bacteria, A. molluscorum Av27 and A. hydrophila ATCC7966, were reported to be resistant (Cruz et al, 2007;Hernould et al, 2008).…”
Section: Bacteriamentioning
confidence: 95%
See 1 more Smart Citation
“…For example, 8.4 µM and 50 µM of TBT were considered the barrier of toxic concentrations by Wuertz et al (1991) (Mendo et al, 2003;Cruz et al, 2007) which can be related with the different architecture of the bacterial cell wall. According to the literature, the highest TBT concentration tested was about 3 mM (Cruz et al, 2007;Hernould et al, 2008). At this concentration two Gram negative bacteria, A. molluscorum Av27 and A. hydrophila ATCC7966, were reported to be resistant (Cruz et al, 2007;Hernould et al, 2008).…”
Section: Bacteriamentioning
confidence: 95%
“…Despite the severe impact of TBT on living organisms, several studies have reported TBT resistant bacteria from water and sediment (Jude et al, 1996;Martins et al, 2005;Dubey et al, 2006;Cruz et al, 2007;Hernould et al, 2008). Suzuki et al (1992) affirm that TBT resistance can be induced by the exposure to TBT and to other metals present in the environment (Suzuki et al, 1992).…”
Section: Bacteriamentioning
confidence: 95%
“…From the available literature a number of mechanisms contributing to TBT resistance have been described and seem to be present within the same strain and also among different strains and species (Dubey et al, 2006;Hernould et al, 2008;Kawai et al, 1998). Some of the mechanisms might be activated at different phases of the bacterial growth and/or when cells are exposed to different TBT concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the mechanisms might be activated at different phases of the bacterial growth and/or when cells are exposed to different TBT concentrations. Likewise, in A. hydrophila it was suggested that in addition to the AheABC system, other RND-type efflux pumps contribute to the intrinsic drug resistance observed in this species (Hernould et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation